2020
DOI: 10.1101/2020.11.18.387787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate traits shape the structure of microbial community engaged in metabolic division of labor

Abstract: Metabolic division of labor (MDOL) is widespread in nature, whereby a complex metabolic pathway is shared between different strains within a community for mutual benefit. However, little is known about how communities engaged in MDOL assemble and spatially organize. We hypothesized that when degradation of an organic compound is carried out via MDOL, substrate concentration and its toxicity modulate the benefit allocation between the two microbial populations, thus governing the assembly of this community. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 96 publications
(189 reference statements)
1
7
0
Order By: Relevance
“…From this perspective, when designing a synthetic consortium engaged in MDOL for pollutant degradation, it may be useful to assign a by-product to the former populations. Thirdly, our results also showed that if the substrate is toxic, the microbial system will be more stable, which is consistent with the results in our previous study 28 . In summary, our results provide a quantitative way to evaluate the feasibility of applying these strategies into a specific pathway engineering, and thus should greatly assist in designing and managing related artificial microbial systems.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…From this perspective, when designing a synthetic consortium engaged in MDOL for pollutant degradation, it may be useful to assign a by-product to the former populations. Thirdly, our results also showed that if the substrate is toxic, the microbial system will be more stable, which is consistent with the results in our previous study 28 . In summary, our results provide a quantitative way to evaluate the feasibility of applying these strategies into a specific pathway engineering, and thus should greatly assist in designing and managing related artificial microbial systems.…”
Section: Discussionsupporting
confidence: 93%
“…[8]-[13] in Methods section). Consistent with our previous hypotheses and observations 28 , we next assumed that P, which was produced by the second population, was the sole resource for the growth of both populations, while neither S nor I could be directly used for growth. As a consequence, [0, 1] possesses a preferential access to the final product (P), resulted in a 'private benefit' derived from the product privatization (Figure 1A).…”
Section: Model Framework For Two-step Mdolmentioning
confidence: 53%
See 3 more Smart Citations